(untitled) (Conferencea, 2022)
This is the place where all business transactions are carried out in the modern economic system. High commercial risks, regulation of market processes at different levels of management, etc. - all this requires the organization of permanent and deep statistical market mechanism research. Statistics allows you to reflect the state of the market, characterize its structure and dynamics, evaluate its fluctuations, identify the complex market factors and build forecasts of its further development. The objectives of statistical market research are to determine the balance of commodity and money supply, the study of supply and demand and their relationship, the characteristics of pricing, management of the range and quality of goods and services, analysis of resources and their use, calculation of the effectiveness of the sales program and promotion program, identification and analysis of socio-economic results and the effectiveness of the functioning of markets.